The Effect of Power Outages on Small- and Medium-sized Enterprises in South Africa - Paul Saah; Charles Mbohwa (Research Synergy Press, 2024)
The frequent power outages in South Africa have had a detrimental impact on the nation’s economy overall and on small and medium-sized enterprises in particular. The goal of this study is to determine how load shedding affects small- and medium-sized enterprises (SMEs) in South Africa. The research design pinpoints practical ways to reduce the negative effects of power outages on these companies. This study adopts a quantitative research approach. Fifty SME owners and managers from the Mahikeng local municipality were selected to represent the entire country using a descriptive single cross-sectional design and a non-probability convenience sample technique. The Statistical Package for the Social Sciences (SPSS), Version 27.0, was used to evaluate the collected data. The findings of the study indicate that load shedding has caused significant operational problems for South African small enterprises since 2008. As a result, to maintain output, many companies have had to make adaptations, including establishing backup power solutions and moving to manual labor. SMEs continue to face significant challenges because of the high cost of backup systems, the increase in criminal activity during blackouts, and the requirement for open and positive customer relations, despite efforts to mitigate these consequences. The present study underscores the criticality of SMEs’ investments in crime prevention strategies and dependable backup power systems in Mafikeng and throughout South Africa to mitigate the adverse impacts of ongoing load shedding on commercial operations and economic stability. It is underlined that maintaining client confidence and ensuring continued business performance despite these challenges requires effective customer relationship management.